Aplikasi Constructed Wetland Sistem Batch Dalam Mereduksi BOD Dan COD Lindi Menggunakan Kangkung Air (Ipomoea Aquatica Forks) - Guntar Marolop Saragih; Siti Umi Kalsum; Reza Bagus Maulana (Jurnal Daur Lingkungan, 2023)
ABSTRAKAir Lindi dihasilkan dari Tempat Pemrosesan Akhir Sampah controlled landfill tidak aktif dengan karakteristik BOD dan COD yang tinggi. Pengolahan air lindi dapat dilakukan dengan menggunakan tumbuhan kangkung air (Ipomoea aquatica forks) pada Constructed Wetland. Penelitian ini bertujuan untuk mengetahui pertumbuhan kangkung air (Ipomea aquatica forks) dan pengaruhnya pada BOD dan COD air lindi dan hubungannya dengan efektifitas Contructed Wetland sistem batch. Proses pertumbuhan kangkung air Pertumbuhan panjang batang sangat berpengaruh dalam menurunkan polutan BOD dan COD pada lindi (leachate). Kangkung air dapat menyerap zat organik melalui ujung akar. Zat organik yang terserap akan masuk ke dalam batang melalui pembuluh pengangkut kemudian menyebar ke seluruh bagian tanaman. Pada proses ini zat organik akan mengalami reaksi biologi dan terakumulasi di dalam batang tanaman dan diteruskan ke daun. Contructed Wetland sistem batch dengan media kangkung air (ipomoea aquatica forks) dapat menurunkan kadar BOD sebesar 86%, COD sebesar 87% pada hari ketujuh. Lalu pada hari keempat belas BOD dan COD turun sebesar 98%.Kata kunci : BOD, COD, Constructed Wetland, Ipomoea Aquatica Forks, Leachate ABSTRACTThe current Inactive Controlled Landfill TPA has been abandoned and is no longer operating. The leachate in the TPA is still flowing and there is no treatment. With no processing of the leachate, the levels of BOD and COD pollutants in the leachate are high. One of the media and methods for reducing BOD and COD pollutants in leachate is using the water spinach plant (ipomoea aquatica forks) and the Constructed Wetland method. The purpose of this study was to determine the growth process of ipomoea aquatica forks as a plant medium in reducing BOD and COD leachate pollutants and then to analyze the effectiveness of the Constructed Wetland batch system with ipomoea aquatica forks media in reducing BOD and COD pollutants in leachate. The process of growing water spinach Stem length growth reduces BOD and COD pollutants in leachate water. Water spinach potentially absorb organic substances through the root tips. Absorbed organic matter translocate the stem through the transport vessels and then spread to all parts of the plant. In this process, organic substances will undergo biological reactions and accumulate in the stems of plants, and be passed on to the leaves. The Constructed Wetland batch system with ipomoea aquatica forks media can reduce BOD levels by 86%, and COD by 87% on the seventh day. Then on the fourteenth day, BOD and COD fell by 98%. Keywords :    BOD, COD, Constructed Wetland, Ipomoea Aquatica Forks, Leachate